Eye movement desensitization and reprocessing (EDMR) therapy : basic principles, protocols, and procedures - Shapiro, Francine (New York : The Guilford Press, 2018)
"Description: The authoritative presentation of Eye Movement Desensitization and Reprocessing (EMDR) therapy, this groundbreaking book--now revised and expanded--has enhanced the clinical repertoires of more than 100,000 readers and has been translated into 10 languages. Originally developed for treatment of posttraumatic stress disorder (PTSD), this evidence-based approach is now also used to treat adults and children with complex trauma, anxiety disorders, depression, addictive behavior problems, and other clinical problems. EMDR originator Francine Shapiro reviews the therapy's theoretical and empirical underpinnings, details the eight phases of treatment, and provides training materials and resources. Vivid vignettes, transcripts, and reproducible forms are included. Purchasers get access to a Web page where they can download and print the reproducible materials in a convenient 8 1/2" x 11" size. Key Words: Eye Movement Desensitization and Reprocessing Therapy, EMDR, eye movements, techniques, posttraumatic stress disorder, PTSD, trauma survivors, trauma treatments, evidence-based treatments, interventions, psychotherapy, adaptive information processing, disorders, addictions, military trauma, moral injury, natural disasters, crime victims,traumatic experiences, therapists, mental health professionals, trauma recovery, EMDR protocols, EMDR manuals, abreactions, trauma therapies, therapy approaches, healing emotional pain, EMDR processing, trauma memory, behavior therapies, behavior therapy, hypnosis, hypnotherapy, brain, EMDR International Association, EMDRIA, books on EMDR, books on psychological trauma, books on trauma recovery, books on PTSD, hand motions,"--
Background -- Adaptive information processing -- Components of EDMR therapy and basic treatment effects -- Phase one: client history -- Phases two and three: preparation and assessment -- Phases four to seven: desensitization, installation, body scan, and closure -- Working with abreaction and blocks -- Phase eight: reevaluation and use of the EDMR therapy standard three-pronged protocol -- Satndardized protocols and procedures for special situations -- The cognitive interweave -- Selected populations -- Theory, research, and clinical implications
Revised edition of: Eye movement desensitization and reprocessing (EMDR) : basic principles, protocols, and procedures. 2nd ed. c2001
Includes bibliographical references and index
Keywords: Eye movement desensitization and reprocessing; Post-traumatic stress disorder -- Treatment; Psychic trauma -- Treatment; Eye Movement Desensitization Reprocessing; Stress Disorders, Post-Traumatic -- therapy; Posttraumatiskt stressyndrom -- psykologiska aspekter